How the integration of phylogenetics and venomics resolves persistent challenges in evolutionary systematics and toxinology lessons from the spider kingdom - Lüddecke, Tim; Justus Liebig University Giessen (My University, 2021)
Spiders represent one of the most successful branches of metazoan life. Throughout their long-lasting evolutionary trajectory, spiders diversified into almost 50,000 species. They conquered all continents except antarctica and established themselves as predators in virtually all ecosystems. The invention of venom systems, that are present in all but one spider lineages, contributed significantly to their evolutionary success. Albeit research on spiders, referred to as Arachnology, is an old field of study, it is hampered by a variety of persistent challenges awaiting scientific resolution. A subset of four such challenges, relating to evolutionary systematics and toxinology, are of pivotal importance. First, the taxonomic status of many spiders, in particular within the mygalomorph infraorder, and their phylogenetics remains largely ambiguous. Secondly, knowledge on spider venoms is so far fully derived from selected taxa and biased towards the few medically significant or exceptionally large species. Third, the sheer diversity of spiders makes it rather difficult to select promising focal taxa for venom bioprospecting studies. Lastly, knowledge upon the evolutionary forces driving spider venom evolution remains in its infancy. Addressing these important issues via phylogenetic and venomic approaches is the scope of this work.Systematic ambiguity is addressed by using tarantulas (Theraphosidae) as a model group. In two experimental setups, a molecular phylogenetic study utilizing six sequenced genes plus a phylogenomic study on ca. 2,000 genes, the first phylogenetic trees for Theraphosidae are constructed. These recovered monophyly of Theraphosidae as a whole and supported validity of formerly questionable subfamilies Poecilotheriinae, Psalmopoeinae and Stromatopelminae. It clarifies the position of Brachionopus and Harpactirella and argues for paraphyly of Schismatothelinae. In a trait evolution analysis, this work finds that defensive hairs likely evolved convergently within neotropical tarantulas. To make bioprospecting studies more efficient, this work developed a phylogeny-driven strategy for rational taxon selection in biodiscovery, exemplified on the proposed tarantula phylogeny. Applying this strategy towards the whole spider kingdom recovered the family Araneidae as especially promising focal group. Consequently, the wasp spider Argiope bruennichi as a member of this family is subsequently studied. A morphological analysis of its venom apparatus found, that gland and chelicerae mirror structures present in the few other studied spider venom apparatuses. However, the venom duct that connects fang and venom gland was found to be substructured into four distinct units, displaying a previously hidden complexity within spider venom systems. A Venomic analysis revealed, that the wasp spider venom is rather simply composed and that CAP proteins dominates the venom profile. As other spider venoms are mostly composed of small neurotoxic peptides, the venom of A. bruennichi is considered as arachno-atypical. This work proposes an evolutionary scenario, in which an economic dilemma between the venom system and the silk system during hunting led to the loss of venom components in the wasp spider. Lastly, a selection of novel biomolecules that mirror insect-neuropeptides are identified within the wasp spider venom, highlighting the underestimated importance of neuropeptides as evolutionary starting points for the birth of toxic components.This work contributes to the field of Arachnology as it significantly advances the status quo within the four selected challenges in evolutionary systematics and toxinology through synthesis of phylogenetics and venomics. It clarifies the taxonomic placement of several spider lineages and proposes the first well supported hypothesis upon tarantula evolution. A novel approach towards a rational taxon selection is developed and explored. As a consequence, the study of an araneid venom expanded the general understanding of spider venoms and the architecture of their venom apparatus beyond the taxonomic bias. The underestimated importance of larger proteins versus small neurotoxic peptides is emphasized and the role of neuropeptides in venom evolution is supported. The role of negative selection in spider venom evolution is discussed in perspective to loss of toxicity in defensive hair-bearing tarantulas and the economic dilemma between both weapon systems in A. bruennichi. This work thus contemplates novel insights and concepts towards the four persistent challenges and provides an experimentally supported framework on which future systematic-, evolutionary-, bioprospective- and general venomic works can be informed upon.
Wie die Integration von phylogenetischen und venomischen Methoden persistente Probleme der evolutionären Systematik und Toxinologie zu lösen vermag - Lektionen aus dem Spinnenreich
Keywords: ddc:630